Research Progress on the Effect of Epilepsy and Antiseizure Medications on PCOS Through HPO Axis - Li, Shuang; Zhang, Linhai; Wei, Nian; Tai, Zhenzhen; Yu, Changyin; Xu, Zucai (Frontiers in Endocrinology, 2021)
Epilepsy is a common chronic neurological disease that manifests as recurrent seizures. The incidence and prevalence of epilepsy in women are slightly lower than those in men. Polycystic ovary syndrome (PCOS), as a reproductive endocrine system disease, is a susceptible to complication in women with epilepsy and its total prevalence is 8%-13% in the female population and sometimes as high as 26% in female epilepsy patients. The main clinical features include chronic anovulation, hyperandrogenemia (HA), and polycystic ovary symptoms, as well as it is usually accompanied by other abnormal changes which are insulin resistance (IR)/hyperinsulinemia and obesity. Valproic acid (VPA) which is effective for most patients with epilepsy, has anticonvulsant and mood-stabilizing effects. However, a meta-analysis showed that the case rate of PCOS increased markedly, in female patients who choose VPA, which was 1.95 times higher than that of other drugs (53), some scholars believe that the increase in incidence is not only related to VPA, but also to epilepsy itself. Epileptiform discharges can affect the activity of the pulse generator located in the hypothalamus, then interfering with the reproductive endocrine system by breaking the balance of the hypothalamic-pituitary-ovarian axis (HPOA), while VPA Interfere with the reproductive endocrine system by affecting the HPOA, IR, increasing body mass, and decreasing hormone conversion and combination.